2010
DOI: 10.1590/s0100-06832010000300031
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different management systems on porosity of oxisols in Paraná, Brazil

Abstract: SUMMARYSoils play a fundamental role in the production of human foods. The Oxisols in the state of Paraná are among the richest and most productive soils in Brazil, but degradation and low porosity are frequently documented, due to intensive farming involving various management strategies and the application of high-tech solutions. This study aims to investigate changes in the porosity of two Red Oxisols (Latossolos Vermelhos), denoted LVef (eutroferric) and LVdf (dystroferric) under conventional and no-tillag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 22 publications
2
8
0
8
Order By: Relevance
“…The Ma data indicated that the CT and NT were very close to this limit (10 %), which suggested that these areas were already affected by limited plant growth. This reinforced previous results that showed how management strategies involving the use of increasingly larger machines without considering the soil moisture content or without crop rotation facilitate short and long-term compaction (Silva et al, 2000;Tavares Filho et al, 2010Baquero et al, 2012;Llanillo et al, 2006Llanillo et al, , 2013. This idea is reinforced in the radial graphs for the proportional values for the 0-50 cm layer for OM, FD, Bd and Ma (Figure 4).…”
Section: Evaluation Of the Soil Morphologysupporting
confidence: 87%
See 3 more Smart Citations
“…The Ma data indicated that the CT and NT were very close to this limit (10 %), which suggested that these areas were already affected by limited plant growth. This reinforced previous results that showed how management strategies involving the use of increasingly larger machines without considering the soil moisture content or without crop rotation facilitate short and long-term compaction (Silva et al, 2000;Tavares Filho et al, 2010Baquero et al, 2012;Llanillo et al, 2006Llanillo et al, , 2013. This idea is reinforced in the radial graphs for the proportional values for the 0-50 cm layer for OM, FD, Bd and Ma (Figure 4).…”
Section: Evaluation Of the Soil Morphologysupporting
confidence: 87%
“…This finding agrees with results of Silva et al (2000) but disagrees with the findings of Silveira et al (1999) and Silveira Neto et al (2006). In addition, these results reinforce the fact that more intensive soil tillage and equipment traffic on the soil surface (especially under inadequate moisture conditions with increased OM degradation on the soil surface) results in greater soil degradation (Neves et al, 2007;Tavares Filho et al, 2010Baquero et al, 2012;Llanillo et al, 2006Llanillo et al, , 2013Calegari et al, 2013).…”
Section: Evaluation Of the Soil Morphologymentioning
confidence: 53%
See 2 more Smart Citations
“…Após a incorporação desses solos ao sistema produtivo problemas de degradação física, sobretudo alterações estruturais e compactação do solo, têm sido observados (Assouline et al, 1997;Tavares Filho et al, 1999, 2001Giarola et al, 2007;Tavares Filho &Tassier, 2009, Tavares Filho & Tessier, 2010 e embora esses problemas possam existir desde o início da agricultura, sua extensão e seu impacto são considerados, hoje, de extrema intensidade (Lal & Stewart, 1990). Portanto, o diagnóstico qualitativo de diferentes estruturas a campo, complementado pelas análises laboratoriais, pode ajudar na tomada de decisão quanto ao tipo de manejo a ser empregado no solo para manutenção ou melhoria da produtividade (Tavares Filho &Tassier, 2009;.…”
Section: Introductionunclassified